Reappraisal of a Road Project in Iran - Tak, Herman G. van der.; Weille, Jan de ([Washington: International Bank for Reconstruction and Development]; distributed by Johns Hopkins Press, Baltimore, 1969)
This book offers a great discussion on how to advance the economic development of the underdeveloped world.
Bibliographical footnotes.
ne 2/03/2018
Loan
Keywords: Roads